2015
DOI: 10.1007/s00428-015-1833-5
|View full text |Cite
|
Sign up to set email alerts
|

The medical autopsy as quality assurance tool in clinical medicine: dreams and realities

Abstract: The purpose of medical autopsy has changed to issues of quality assurance today. In addition, autopsies are considered valuable in medical education, e.g., delivering cases for problem-based learning for students. Many studies underscore the need for autopsies also in the era of technical progress emphasizing the continuing discrepancies between antemortem and post mortem diagnoses. Despite these important tasks, we face a decline of autopsy for several reasons with complex interactions. The role of all person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 33 publications
1
69
0
Order By: Relevance
“…Nevertheless, the findings of the present study were in keeping with findings from other large centers, which found discrepancy rates of 15 to 40% [2,6,7,26,27]. Despite advances in medical technology, the frequency of major discrepancies between clinical diagnoses and diagnoses based on pathologic findings-including autopsy-has not changed [3].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, the findings of the present study were in keeping with findings from other large centers, which found discrepancy rates of 15 to 40% [2,6,7,26,27]. Despite advances in medical technology, the frequency of major discrepancies between clinical diagnoses and diagnoses based on pathologic findings-including autopsy-has not changed [3].…”
Section: Discussionsupporting
confidence: 89%
“…As well, radiologists admit that at present the technology is not yet good enough to provide as much detail as a conventional postmortem examination. accepted among Jewish, Christian and Muslim communities [30,31] and is preferable to no postmortem examination at all [2,17].…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments are non-(or minimally invasive) post-mortem imaging techniques to detect coronary occlusion and ischemic injury in order to serve as an adjunct to, or even to replace, cardiac autopsy with presumed ischemic death [6,7]. These novel post-mortem approaches presently attract much interest; autopsy rates tend to decrease gradually in many countries [8].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical autopsies are also becoming increasingly rare as they are often considered expensive, time-consuming, a potential source of medico-legal dispute, and a violation of the dignity of the deceased [5,6]. Consequently, Italian surgeons are often forced to import human cadavers or to go abroad to attend training courses, which involves high costs and professional and personal discomfort [7,8].…”
Section: Introductionmentioning
confidence: 99%